The Influence of Artsteps Virtual Museum Learning Media on the History Learning Outcomes of Grade XI Students of Eria Medan Private High School - Sibarani, Esmin Yuliana; Tanjung, Samsidar; Sianturi, Rheinhard Sam; Sitepu, Putri Sri Binda Br. (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of the use of the Artsteps Virtual Museum learning media on the history learning outcomes of class XI students at Eria Medan Private High School. The method used is a quantitative descriptive study with a Quasi-Experimental design through a pretest-posttest control group design model. The study population included all class XI students at Eria Medan Private High School, with a saturated sampling technique so that the entire population of 50 students was sampled. Data were collected through multiple-choice pretest and posttest tests that had passed validity, reliability, difficulty level, and discriminatory power tests. Data analysis included normality tests, homogeneity tests, and hypothesis tests using independent sample t-tests. The results showed a difference in the average posttest score, where the experimental class obtained an average of 86.88 which was higher than the control class of 68.48, with a significance value of 0.001. This proves that there is a significant influence. Thus, it can be concluded that the use of the Artsteps Virtual Museum media has a positive and significant effect on the history learning outcomes of class XI students at Eria Medan Private High School